Progress in Silk Fibroin Based Composite Scaffold/Hydrogel: Silk Fibroin/PEG Hydrogel for the RPE Regeneration a Promising Biomaterial for Clinical Application - Jeong, Yong Woon; Kim, Han Sol; Thangavelu, Muthukumar; Choi, Min Joung; Lee, Gi Won; Song, Cheol Ui; Song, Jeong Eun; Khang, Gilson (Frontiers in Materials, 2020)
Retinal pigment epithelium (RPE) plays a decisive role in the normal function of the retina, especially in the maintenance of photoreceptors. RPE dysfunction, loss of sight and degeneration has been implicated as the cause of many retinal diseases including pigmented retinitis and age-related macular degeneration (AMD). Silk fibroin (SF) is a biodegradable natural polymer with biocompatibility, non - toxic and non - immunological properties. In this study, hydrogel material was prepared by mixing it with PEG [poly (ethylene glycol)] a synthetic polymer. SF hydrogel (SH) and with PEG (SPH) were prepared with different sonication times. The SH and SPH were prepared with different sonication time (20s SH, 30s SH, 20s SPH, and 30s SPH were prepared respectively. The prepared SH and SPH were physio chemically characterized by SEM, FTIR, compressive strength, porosity and in vitro biocompatibility were analyzed using MTT assay along with cell adhesion and cell proliferation, their gene expression was analyzed using RT-PCR. As a result, the 20s SPH hydrogel exhibited superior biocompatibility, cell adhesion, and improved cell growth compared to pure SH. Their respective genes expression for retinal function and matrix production was also positively influenced by 20s SPH with an increase in gene expression folds of RPE65, CRALBP. The obtained results suggest that the 20s SPH hydrogel can be used as an alternative material for the application of retinal regeneration and delivery.